English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3/n-5 - 1/5-n Need help solving this problem....need to find common demoninator first...thanks

2007-01-12 13:50:13 · 6 answers · asked by gail 1 in Science & Mathematics Mathematics

6 answers

OK...5-n is equal to (n-5)*(-1), therefore your problem is:

3/n-5 + 1/n-5. Obviously this is 4/n-5.

The long way:

3/n-5- 1/5-n= (15-3n-n+5)/(n-5)(5-n)
=(20-4n)/(n-5)(5-n)
=4(5-n)/(n-5)(5-n)
=4/n-5

2007-01-12 14:02:20 · answer #1 · answered by samuelll 2 · 0 0

Note: 5 - n = - (- 5 + n) = - (n - 5)

3/(n-5) - 1/(5-n)
= 3 / (n - 5) - 1 / [ -(n - 5)]
= 3 / (n - 5) + 1 / (n - 5)
=(3 + 1) / (n - 5)
= 4 / (n - 5)

2007-01-12 22:00:31 · answer #2 · answered by Sheen 4 · 0 0

You can simplifty the above expression to another level:

(-4n+20/(n-5)-(n-5) = -4(n-5)/-1(n-5)^2 = 4/n-5.

2007-01-12 22:06:11 · answer #3 · answered by Dr Dave P 7 · 0 0

(3/(n - 5)) - (1/(5 - n))
(3/(n - 5)) - (1/(-n + 5))
(3/(n - 5)) - (1/(-(n - 5)))
(3/(n - 5)) + (1/(n - 5))
(3 + 1)/(n - 5)
4/(n - 5)

2007-01-12 23:12:19 · answer #4 · answered by Sherman81 6 · 0 0

The common denominator is (n-5)(5-n).

So, we have in the numerator 3(5-n) - 1(n-5) = 15 - 3n - n + 5 = -4n + 20

So the final answer is (-4n+20)/[(n-5)(5-n)]

2007-01-12 21:53:27 · answer #5 · answered by JasonM 7 · 0 0

the answer is 2/1.

1/5-n can be switched arount to n+5....
so 1/n+5

so n-5 - n+5... you add... which simply equals 1.

3-1 = 2.

so 2/1

2007-01-12 23:52:38 · answer #6 · answered by locke32080 1 · 0 0

fedest.com, questions and answers